Persepsi Wajib Pajak Terhadap Pajak Penghasilan PP No. 23 Tahun 2018 (Studi UMKM Kabupaten Maybrat) - Way, Anetha; Wulandary, Alyn (Multidisciplinary Journal of Education , Economic and Culture, 2025)
This study aims to analyze the knowledge and understanding of Micro, Small, and Medium Enterprises Taxpayers regarding taxation according to Government Regulation Number 23 of 2018 in Maybrat Regency. This study was conducted through Observation, Interviews, and Documentation of Research Results that the level of knowledge and understanding of MSME Taxpayers regarding the implementation of Government Regulation Number 23 of 2018 is still too minimal, because some of the Business Taxpayers. The results of the study showed that there were MSME actors who stated that they knew about the collection of Article 11 Income Tax for various reasons, there were already tax collection rates but they did not really understand the calculation of taxes, so it can be concluded that the socialization of MSME taxes is still lacking. There is no ease and simplification in tax collection. According to the MSME actors that the researcher met, in paying taxes to tax officers it is said to be fair if the profits obtained are large